Modified polyethylene fiber as well as preparation method and application thereof
By surface modification of polyethylene fiber and the use of silane coupling agents and other chemical substances to enhance its surface properties, the problem of poor bonding performance of polyethylene fiber is solved, high-strength interfacial bonding with the concrete matrix is achieved, and the Mechanical properties of fiber concrete.
Patent Information
- Application Number
- CN202411221285.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-21
AI Technical Summary
The smooth surface, non-polarity and low surface energy of polyethylene fibers lead to poor adhesion to other materials, limiting their application in many fields.
The surface modification of polyethylene fibers is coordinated by collaborative use of silane coupling, ethanol, ionic water, nano -sanxia, dopamine hydrochloride, and trivytic oxyl oxyl aminamide, and improves its surface performance and bonding performance.
The modified polyethylene fiber has enhanced interface properties, improved hydrophilicity and lower cost, which can significantly improve the interface bonding strength between it and the concrete matrix, thus improving the mechanical properties of fiber concrete.
Smart Images

Figure CN119332504A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional fibers, and particularly relates to a modified polyethylene fiber and a preparation method and application thereof. Background Art
[0002] Polyethylene fiber is a widely used synthetic fiber with good wear resistance, tensile strength and chemical stability. However, due to its smooth surface, non-polarity and low surface energy, its bonding performance with other materials is poor, which limits its application in many fields. Therefore, modifying the surface of polyethylene fiber to improve its surface properties and bonding properties is an important research direction.
[0003] The main methods for polyethylene fiber surface modification include physical modification, chemical modification, surface coating, surface plasma treatment, high-energy radiation treatment, etc.
[0004] Physical modification: Changing the morphology and structure of the polyethylene fiber surface through physical methods, such as surface roughening, surface etching, etc. This method can increase the roughness of the fiber surface and increase the contact area with other materials, thereby improving the bonding performance. However, physical modification may affect the mechanical properties of the fiber, and the modification effect is unstable.
[0005] Chemical modification: It is to introduce polar groups or functional groups on the surface of polyethylene fibers through chemical reactions, such as anhydrides, ketones, aldehydes, etc. These groups form chemical bonds or hydrogen bonds to improve the bonding performance. Chemical modification methods include surface oxidation, surface grafting, etc. Chemical modification has a good effect, but it may affect the mechanical properties and thermal stability of the fiber.
[0006] Surface coating method: a layer of material with good bonding properties, such as polyurethane, epoxy resin, etc., is coated on the surface of polyethylene fiber. This method can improve its surface properties without changing the properties of the fiber itself, but the coating may fall off during use, affecting its long-term stability.
[0007] Surface plasma treatment: plasma is used to treat the surface of polyethylene fibers to introduce polar groups or functional groups. This method can be carried out at low temperatures and has little effect on the mechanical properties of the fibers, but the equipment investment is large and the cost is high.
[0008] High-energy radiation treatment is to treat polyethylene fibers with high-energy rays (such as ultraviolet rays, gamma rays, etc.) to introduce polar groups or functional groups. This method can be carried out without contacting the fibers and has little effect on the mechanical properties of the fibers, but the radiation dose is difficult to control and may damage the fibers.
[0009] The existing methods for modifying the surface of polyethylene fibers have their own advantages and disadvantages, and it is necessary to select a suitable modification method according to the actual application requirements. At the same time, the modification methods in the existing technology still have some limitations, such as unstable modification effect, affecting the mechanical properties of the fiber, and high cost. Summary of the invention
[0010] In view of the problems of the prior art, the technical problem to be solved by the present invention is to provide a modified polyethylene fiber and its preparation method and application. The present invention proposes to use silane coupling agent, ethanol, deionized water, nano-silicon dioxide, dopamine hydrochloride and trishydroxymethylaminomethane to synergistically modify the surface of polyethylene fiber, thereby improving the various properties of PE fiber. The method is simple and low in cost. It not only changes the PE fiber from non-polar to polar, but also, due to the presence of nano-silicon dioxide and dopamine hydrochloride, the fiber surface can also have a coating and roughness, which can greatly increase the interfacial bonding strength between the fiber and the concrete matrix, thereby improving the various mechanical properties of the fiber concrete, and also greatly reducing the fiber content and reducing the cost of use.
[0011] The fiber modification material is a mixture of one or more of deionized water, KH550, dopamine hydrochloride, Tris, and nano-silicon dioxide.
[0012] The present invention provides a method for preparing a modified polyethylene fiber, comprising:
[0013] (1) mixing water, a silane coupling agent and an alcohol, and subjecting the mixture to ultrasonic treatment to obtain a solution A;
[0014] (2) mixing dopamine hydrochloride, tris(hydroxyaminomethane) Tris, and water, and stirring to obtain solution B;
[0015] (3) mixing the nanomaterial and water to obtain solution C;
[0016] (4) The polyethylene fiber is first immersed in solution A, heated in a water bath, dried, and then immersed in solution B, stirred, and dried;
[0017] Then, the fiber is immersed in solution C, stirred, and dried to obtain modified polyethylene fiber.
[0018] Preferably, in step (1), the silane coupling agent is one or more of KH550, KH560, and KH570; the alcohol is one or more of methanol, propanol, and ethanol; and the water is deionized water;
[0019] Preferably, the volume ratio of water, silane coupling agent and alcohol is (35-45):(5-15):(1-5).
[0020] Preferably, the ultrasonic treatment in step (1) is carried out at an ultrasonic frequency of 5-8 KHZ and a temperature of 0-50° C. for 10-30 min under open conditions.
[0021] Preferably, in step (2), the mass ratio of dopamine hydrochloride to tris(hydroxyaminomethane) Tris is (2.5-7.5):(1-3); and the pH value of solution B is 8-9.
[0022] Preferably, the nanomaterial in step (3) is at least one of nano-silicon dioxide and nano-calcium carbonate; and the concentration of the nanomaterial in solution C is 3-5 g / L.
[0023] Preferably, in step (4), the sample is immersed in solution A for heating treatment and drying, wherein the heating treatment temperature is 40-70°C for 4-8 hours; and the drying temperature is 40-70°C for 6-12 hours.
[0024] Preferably, in step (4), the mixture is immersed in solution B, stirred, and dried, wherein the stirring temperature is 40-70°C, the time is 6-12h, the stirring speed is 200-500r / min, and the stirring is carried out by a magnetic stirrer; the drying temperature is 40-70°C, and the time is 6-12h.
[0025] Preferably, in step (4), the mixture is immersed in solution C, stirred, and dried, wherein the stirring temperature is 40-70°C, the stirring speed is 200-500 r / min, the time is 6-12 h, and the stirring is carried out by a magnetic stirrer; the drying temperature is 40-70°C, and the time is 6-12 h.
[0026] The polyethylene fiber in step (4) is an ultra-high molecular weight polyethylene fiber, wherein the molecular weight is 1-6 million.
[0027] The invention provides a modified polyethylene fiber prepared by the method.
[0028] The invention provides concrete, wherein the concrete contains the modified polyethylene fiber.
[0029] The concrete components include: materials and water;
[0030] The material components include: 40-60% cement, 4-8% mineral powder, 4-8% fly ash, 20-40% river sand, 1-5% expansion agent, 0.01-1% water reducer, 0.01-1% boric acid, 0.1-0.8% shrinkage reducer, 0.2-1% modified polyethylene fiber. The water accounts for 20-40% of the material mass.
[0031] Beneficial Effects
[0032] The present invention improves the performance of ultra-high molecular weight polyethylene (UHMWPE) fiber or gives it new functions by chemically modifying it. Compared with the original fiber, the modified UHMWPE fiber has the following advantages and positive effects:
[0033] (1) Enhanced interface performance: The interface bonding strength between UHMWPE fiber and concrete can be enhanced by chemical surface modification of PE fiber. High ductility concrete was prepared using fibers before and after modification. The equivalent bending toughness of fiber concrete before modification was 222.84KJ / m 3 The equivalent bending toughness of the fiber concrete prepared by the modified fiber is 338.14KJ / m 3 , which is 1.5 times that before modification, which is the reason for the improvement of the interfacial bonding strength between the fiber surface and concrete.
[0034] (2) Improved hydrophilicity: The original UHMWPE fiber is hydrophobic with a contact angle of 143°, while the contact angle of the modified fiber is 13°.
[0035] (3) Lower cost: Since the equivalent bending toughness of the modified fiber is 1.5 times that of the unmodified fiber at the same dosage, when the equivalent bending toughness of the two is the same, the amount of modified fiber used is only 70% of that of the unmodified fiber, which greatly reduces the cost of use.
[0036] In summary, by modifying UHMWPE fibers, their performance and application range can be significantly improved. These modification technologies provide UHMWPE fibers with more possibilities, enabling them to meet the ever-changing industrial and consumer needs.
[0037] The present invention aims to provide a more efficient, stable, environmentally friendly, simple and low-cost polyethylene fiber surface modification method.
[0038] The present invention relates to a surface chemical modification method of ultra-high molecular weight polyethylene fiber, comprising the following components: silane coupling agent, ethanol, deionized water, nano-silicon dioxide, dopamine hydrochloride and tris(hydroxymethyl)aminomethane. The method can improve the hydrophilicity of ultra-high molecular weight polyethylene fiber by modifying the surface of the material, changing it from non-polar to polar. Meanwhile, the presence of nano-silicon dioxide and dopamine hydrochloride can also make the fiber surface have coating and roughness, which can greatly increase the interfacial bonding strength between the fiber and the concrete matrix. The specific data are as follows: Figure 5 shown. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a flow chart of the preparation method of modified PE fiber (Example 3);
[0040] Figure 2SEM microscopic images of the modified PE fibers (c, d) and normal PE fibers (a, b) of Example 3;
[0041] Figure 3 The contact angle comparison between the modified PE fiber (c, d) and the normal PE fiber (a, b) of Example 3;
[0042] Figure 4 Mechanical curve analysis of concrete prepared with modified fibers from Example 3 and normal unmodified fibers;
[0043] Figure 5 The single fiber interface drawing curve in Example 3;
[0044] Figure 6 Performance data of Examples 1-4; DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0046] The polyethylene fibers in all the following examples are TP-1 fiber models provided by Hunan Zhongtai Special Equipment Co., Ltd.
[0047] KH550, dopamine hydrochloride, nano-silica, and Tris were all purchased from Sinopharm Group.
[0048] The water was homemade deionized water.
[0049] Example 1
[0050] A surface chemical modification method for ultra-high molecular weight polyethylene fiber comprises the following steps:
[0051] Step (1) deionized water, KH550 and ethanol are mixed uniformly in a volume ratio of 35:10:5, and ultrasonic treatment is performed at a frequency of 5 kHz and a temperature of 35° C. for 30 min to obtain solution A;
[0052] Step (2) placing the original PE fiber into solution A in a water bath at 40°C for 6 hours, and drying at 60°C for 6 hours to obtain PE-1;
[0053] Step (3) dopamine hydrochloride and trihydroxyaminomethane are mixed in a mass ratio of 5:2, added into deionized water and stirred evenly to obtain a solution B;
[0054] Step (4) PE-1 was placed in solution B and stirred at a temperature of 50°C for 6 hours at a stirring speed of 300 r / min, and then dried at 70°C for 6 hours to obtain PE-2.
[0055] Step (5) adding 5 g of nano-silicon dioxide into deionized water and mixing evenly to obtain a solution C with a concentration of 5 g / L;
[0056] Step (6) PE-2 was placed in solution C and stirred at a speed of 300 r / min at room temperature for 6 hours. The solution was taken out and dried at 70° C. for 6 hours to obtain the final product PE-3.
[0057] The concrete components include materials and water; the material components are: 50.61% cement, 6.45% mineral powder, 6.45% fly ash, 32.3% river sand, 3.233% CSA expansion agent, 0.082% water reducer, 0.075% boric acid, 0.3% shrinkage reducer, 0.5% modified polyethylene fiber PE-3; the water is 20% of the material mass. After the material and water are mixed, they are placed in a 40*40*160 (mm) mold, demolded after one day and placed in a curing box for 28 days of standard curing. Then a universal testing machine is used to test its compressive strength. Conclusion: The maximum load is 9637.27N.
[0058] Example 2
[0059] A surface chemical modification method for ultra-high molecular weight polyethylene fiber comprises the following steps:
[0060] Step (1) deionized water, KH550 and ethanol are mixed uniformly in a volume ratio of 30:15:10, and ultrasonic treatment is performed at a frequency of 6 kHz and a temperature of 40° C. for 25 min to obtain solution A;
[0061] Step (2) placing the original PE fiber into solution A in a water bath at 45°C for 7 hours, and drying at 50°C for 7 hours to obtain PE-1;
[0062] Step (3) dopamine hydrochloride and trihydroxyaminomethane are mixed in a mass ratio of 6:3, added into deionized water and stirred evenly to obtain a solution B;
[0063] Step (4) PE-1 was placed in solution B and stirred at a temperature of 55°C, a stirring time of 7 hours, and a stirring speed of 350 r / min, and then dried at 70°C for 6 hours to obtain PE-2.
[0064] Step (5) adding 5 g of nano-silicon dioxide into deionized water and mixing evenly to obtain solution C;
[0065] Step (6) PE-2 was placed in solution C and stirred at a speed of 350 r / min for 7 h. The solution was taken out and dried at 70° C. for 7 h to obtain the final product PE-3.
[0066] The concrete components include materials and water; the material components include: 50.61% cement, 6.45% mineral powder, 6.45% fly ash, 32.3% river sand, 3.233% CSA expansion agent, 0.082% water reducer, 0.075% boric acid, 0.3% shrinkage reducer, 0.5% modified polyethylene fiber PE-3; wherein the water is 20% of the material mass. After the material and water are mixed, they are placed in a 40*40*160 (mm) mold, demolded after one day and placed in a curing box for 28 days of standard curing. Subsequently, a universal testing machine is used to test its compressive strength. Conclusion: The maximum load is 9963.72N
[0067] Example 3
[0068] A surface chemical modification method for ultra-high molecular weight polyethylene fiber comprises the following steps:
[0069] Step (1) deionized water, KH550 and ethanol are uniformly mixed in a volume ratio of 40:5:5, and ultrasonic treatment is performed at a frequency of 7 kHz and a temperature of 60° C. for 10 min to obtain solution A;
[0070] Step (2) placing the original PE fiber into solution A in a water bath at 60° C. for 6 hours, and drying at 60° C. for 6 hours to obtain PE-1;
[0071] Step (3) dopamine hydrochloride and trihydroxyaminomethane are mixed in a mass ratio of 6.5:3.5, added into deionized water and stirred evenly to obtain a solution B;
[0072] Step (4) PE-1 was placed in solution B and stirred at 60°C for 6 hours at a stirring speed of 400 r / min, and then dried at 60°C for 6 hours to obtain PE-2.
[0073] Step (5) adding 5 g of nano-silicon dioxide into deionized water and mixing evenly to obtain solution C;
[0074] Step (6) PE-2 was placed in solution C and stirred at a speed of 400 r / min for 6 h. The solution was taken out and dried at 60° C. for 6 h to obtain the final product PE-3.
[0075] The concrete components include materials and water; the material components include: 50.61% cement, 6.45% mineral powder, 6.45% fly ash, 32.3% river sand, 3.233% CSA expansion agent, 0.082% water reducer, 0.075% boric acid, 0.3% shrinkage reducer, and 0.5% modified polyethylene fiber PE-3; wherein the water accounts for 20% of the material mass. After the material and water are mixed, they are placed in a 40*40*160 (mm) mold, demolded after one day, and placed in a curing box for 28 days of standard curing. Subsequently, a universal testing machine is used to test its compressive strength. Conclusion: The maximum load is 11280.13N. The equivalent bending toughness of fiber concrete is 338.14KJ / m 3 .
[0076] Example 4
[0077] Step (1) deionized water, KH550 and ethanol are mixed uniformly in a volume ratio of 25:15:10, and ultrasonic treatment is performed at a frequency of 8 kHz and a temperature of 15° C. for 10 min to obtain solution A;
[0078] Step (2) placing the original PE fiber into solution A in a water bath at 55°C for 8 hours, and drying at 50°C for 8 hours to obtain PE-1;
[0079] Step (3) dopamine hydrochloride and trihydroxyaminomethane are mixed in a mass ratio of 7:2.5, added into deionized water and stirred evenly to obtain a solution B;
[0080] Step (4) PE-1 was placed in solution B and stirred at a temperature of 58°C, a stirring time of 9 hours, and a stirring speed of 350 r / min, and then dried at 65°C for 8 hours to obtain PE-2.
[0081] Step (5) adding 4.5 g of nano-silicon dioxide into deionized water and mixing well to obtain solution C;
[0082] Step (6) PE-2 was placed in solution C and stirred at a speed of 350 r / min for 8 h. The mixture was taken out and dried at 65° C. for 8 h to obtain the final product PE-3.
[0083] The concrete components include materials and water; the material components are: 50.61% cement, 6.45% mineral powder, 6.45% fly ash, 32.3% river sand, 3.233% CSA expansion agent, 0.082% water reducer, 0.075% boric acid, 0.3% shrinkage reducer, 0.5% modified polyethylene fiber PE-3; the water is 20% of the material mass. After the material and water are mixed, they are placed in a 40*40*160 (mm) mold, demolded after one day and placed in a curing box for 28 days of standard curing. Then a universal testing machine is used to test its compressive strength. Conclusion: The maximum load is 7128.41N.
Claims
1. A method for preparing a modified polyethylene fiber, comprising: (1) mixing water, a silane coupling agent, and an alcohol, and subjecting the mixture to ultrasonic treatment to obtain a solution A; (2) mixing dopamine hydrochloride, tris(hydroxyaminomethane) Tris, and water, and stirring to obtain solution B; (3) mixing the nanomaterial and water to obtain solution C; (4) The polyethylene fiber is first immersed in solution A for heating treatment and drying, then immersed in solution B for stirring and drying treatment; then immersed in solution C for stirring and drying to obtain modified polyethylene fiber.
2. The preparation method according to claim 1, characterized in that: In the step (1), the silane coupling agent is one or more of KH550, KH560, and KH570; the alcohol is one or more of methanol, propanol, and ethanol; the water is deionized water; the volume ratio of water, silane coupling agent, and alcohol is (35-45):(5-15):(1-5); The ultrasonic treatment in step (1) is carried out at a frequency of 5-8 KHZ and a temperature of 0-50° C. for 10-30 min.
3. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of dopamine hydrochloride to tris(hydroxyaminomethane) Tris is (2.5-7.5):(1-3); the pH value of the solution B is 8-9.
4. The preparation method according to claim 1, characterized in that: The nano material in step (3) is at least one of nano silicon dioxide and nano calcium carbonate; the concentration of the nano material in solution C is 3-5 g / L.
5. The preparation method according to claim 1, characterized in that: In the step (4), the mixture is immersed in solution A for heating treatment and drying, wherein the heating treatment temperature is 40-70° C. and the time is 4-8 hours; and the drying temperature is 40-70° C. and the time is 6-12 hours.
6. The preparation method according to claim 1, characterized in that: In the step (4), the mixture is immersed in solution B, stirred, and dried, wherein the stirring temperature is 40-70°C, the time is 6-12h, and the stirring speed is 200-500r / min; the drying temperature is 40-70°C, and the time is 6-12h.
7. The preparation method according to claim 1, characterized in that: In the step (4), the mixture is immersed in solution C, stirred, and dried, wherein the stirring temperature is 40-70° C., the stirring speed is 200-500 r / min, and the time is 6-12 h; the drying temperature is 40-70° C., and the time is 6-12 h.
8. A modified polyethylene fiber prepared by the method of claim 1.
9. A concrete, characterized in that: The concrete contains the modified polyethylene fiber according to claim 9.
10. The concrete according to claim 9, characterized in that: The concrete components include: materials and water; the material components include: 40-60% cement, 4-8% mineral powder, 4-8% fly ash, 20-40% river sand, 1-5% expansion agent, 0.01-1% water reducer, 0.01-1% boric acid, 0.1-0.8% shrinkage reducer, 0.2-1% modified polyethylene fiber; the water accounts for 20-40% of the mass of the materials.
Citation Information
Cited By
Deep coal bed gas well cementation cement paste and preparation method thereof
CN120757336A
Deep coal bed gas well cementing slurry and preparation method thereof
CN120757336B